KELAYAKAN HIDUP PETANI DITINJAU DARI PENDAPATAN USAHATANI PADI SAWAH YANG MENGGUNAKAN SISTEM SUBAK PADA SUBAK PURA SARI DI KOTA BAUBAU - Ajo, Antasalam; Wardita, Kadek (Media Agribisnis, 2018)
The most important thing for farmers is the life feasibility guarantee of farming holding. Because this is the most fundamental measure of farming activity. Therefore, the efforts of farmers so that farming activities that have been able to fulfill their life's needs in a decent way continue to be important issues and become attentive to the future. At the Balinese Hindu community, the Subak system is maintained for long because it is able to lift the welfare level of farmers. This system regulates life among farmers, as irrigation is done fairly and evenly, discussing planting time, and the type of rice to be planted. If there is a breach, the ceremony is determined by the ceremonies of the citizen or ritual held in the temple. This research aims to measure the life feasibility of farmers based on the income level of rice farmers who implement the Subak system at Subak Pura Sari in Baubau Town. The results showed that the life feasibility of farmers was achieved because the average farmer's income was above the regional minimum wage (UMR) in southeast Sulawesi, which amounted to IDR 2,002,625 per month in 2017. With total admission IDR 21,930,000 minus total cost IDR Rp 9,162,648, then big farmer income is IDR 12,767,352 per planting season in the form of rice or IDR 3,191,838 per month.  Keywords: life feasibility, the Subak system, farming income